Implementation of virtual primary care: a comparative study of family medicine residents’ experiences (Canadian Medical Education Journal, 2025)
Background: Virtual care (VC) was rapidly adopted during the COVID-19 pandemic to ensure continuity of primary care. In this study, we explored Family Medicine (FM) residents’ evolving experiences with VC across early (2020), late (2022), and post-pandemic (2024) phases in Saskatchewan, focusing on satisfaction, preparedness, supervision, and perceived impact on training and well-being.Methods: FM residents across eight distributed sites were surveyed at three time points using a standardized tool. Responses were analyzed using chi-square, Kruskal-Wallis, and post hoc Mann-Whitney U tests (p < 0.05).Results: Seventy-eight residents participated (2020: n = 26; 2022: n = 19; 2024: n = 33). Satisfaction with VC tended to decline over time (p = 0.074), while requests for additional VC training did not change (p = 0.269). Confidence to use VC post-residency dropped significantly from 100% (2020) to 60.6% (2024; p < 0.001), despite a consistent and moderate amount of supervision. The negative impact of COVID-19 on training declined by 2024 (p = 0.008), while trust in the provincial response to the COVID-19 pandemic also decreased (p < 0.0001).Conclusions: Although FM residents adapted to VC during the pandemic, long-term sustainability to use VC requires improved training, structured supervision, and curricular integration. Embedding VC competencies into postgraduate education is essential to support hybrid models of care in the evolving primary care landscape.